POTENTIAL INSECT PESTS ON ZINGIBERACEAE - YAYUK R SUHARDJNO; SOENARTONO ADISOEMARTO (Treubia, 1986)
On some species of Zingiberaceae, observation have been done to record the possible insect pests on these host plants. Among the many species observed that cause damage ion parts of these zingiberaceous plants, five were observed to show potentials as serious pests. These were Attacus atlas, Kirana diocles, Xanthoptera sp., Jamides alecto and Prodioctes sp, However, based on the usefulness of the plant parts damaged, only one species could be considered as the dangerous pest that had to be handled carefully. This was Prodioctes sp. For other species, the need of further researches covers monitoring the population behaviour which is related to population out rreak, so that preventive action can be measured.